Regional Development and Governance in Hungary - Pálné Kovács, Ilona (Discussion Papers, 2012)
The paper’s aim is to analyse the interdependencies of territorial public administration and regional development policy in Hungary. The legislation on local governments has been impacted mostly by political values like autonomy, closeness to the citizens due to the attitude of legislators during the systemic changes. There are four aspects in which the Hungarian system of local governments dif¬fers from the Western European trends: too small municipalities, too weak coun¬ties, to large and powerful state sector in the territorial tier and too few associa¬tions. Because of these structural features the Act on Local Government was unable to guarantee the decentralisation, thus the local self-government sector could not become a dominant element of territorial administration. The contradictory structure of the medium tier, the weak position of territorial self-govern-ment not only caused disturbances in territorial administration but contributed to the over centralisation of the government’s regional development policy. The special act on regional development was passed in 1996 in the spirit of European regional policy following principles like regionalism, partnership etc. Although the government realised the advantages of decentralisation it re¬mained reluctant to share its competencies in regional policy with the directly elected county government. Instead it introduced special institutions, so called development councils - at four NUTS levels. The fragmented system could not counterbalance the dominance of the central government, the regional policy remained centralised projecting the weaknesses of regional policy adaptation during the preparation process for EU membership.